2018
DOI: 10.1038/s41598-018-20922-z
|View full text |Cite
|
Sign up to set email alerts
|

Early life exposure to ethinylestradiol enhances subsequent responses to environmental estrogens measured in a novel transgenic zebrafish

Abstract: Estrogen plays fundamental roles in a range of developmental processes and exposure to estrogen mimicking chemicals has been associated with various adverse health effects in both wildlife and human populations. Estrogenic chemicals are found commonly as mixtures in the environment and can have additive effects, however risk analysis is typically conducted for single-chemicals with little, or no, consideration given for an animal’s exposure history. Here we developed a transgenic zebrafish with a photoconverta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…Experiments conducting repeated exposures for various chemicals have resulted in either increased or decreased sensitivity when organisms were re-exposed compared to the naïve response. When exposed to 17α-ethinyloestradiol during the first 48 h of development, zebrafish show increased sensitivity to subsequent oestrogen exposures later in development (Green et al 2018 ), and similar results were observed following intermittent exposures to 17α-ethinyloestradiol in roach (Lange et al 2009 ). Higher concentrations of fenvalerate were recorded in intermittently exposed trout as opposed to those continuously exposed (Curtis et al 1985 ), and pulsed exposures to copper during early development were also shown to be more toxic than a continuous exposure at the same concentration (Boyle et al 2020 ).…”
Section: Introductionmentioning
confidence: 72%
“…Experiments conducting repeated exposures for various chemicals have resulted in either increased or decreased sensitivity when organisms were re-exposed compared to the naïve response. When exposed to 17α-ethinyloestradiol during the first 48 h of development, zebrafish show increased sensitivity to subsequent oestrogen exposures later in development (Green et al 2018 ), and similar results were observed following intermittent exposures to 17α-ethinyloestradiol in roach (Lange et al 2009 ). Higher concentrations of fenvalerate were recorded in intermittently exposed trout as opposed to those continuously exposed (Curtis et al 1985 ), and pulsed exposures to copper during early development were also shown to be more toxic than a continuous exposure at the same concentration (Boyle et al 2020 ).…”
Section: Introductionmentioning
confidence: 72%
“…fluorescent proteins or luciferase) is under control of either 1) the endogenous promoter/enhancer of an estrogen inducible gene: e.g. vitellogenin1 ( vtg1 ) ( Chen et al, 2010 ; Abdelmoneim et al, 2020 ), cyp19a1b ( Tong et al, 2009 ), or 2) the synthetic tandem repeats of estrogen responsive element (ERE) which can be activated by the binding of estrogens/eEDCs and ERs ( Legler et al, 2002 ; Gorelick and Halpern, 2011 ; Lee et al, 2012a ; Lee et al, 2012b ; Green et al, 2016 ; Moreman et al, 2017 ; Green et al, 2018 ; Moreman et al, 2018 ). These estrogen biosensors induce a reporter gene expression in response to steroidal estrogens and also eEDCs, which can be detected non-invasively via imaging.…”
Section: Tg Zebrafish As Nam For Assessing Eedc-related Developmental...mentioning
confidence: 99%
“…They include a line generated through crossing tg ( ERE:Gal4ff ; UAS:GFP ) with a pigment free mutant zebrafish Casper ( Green et al, 2016 ), a line where the UAS:GFP has been substituted with another UAS: reporter gene , Kaede ( Green et al, 2018 ), a line tg [ ERE:Gal4ff ; UAS:nitroreductase (NTR)- mCherry ] (shortened name ERE:mCherry ), that enables NTR-mediated chemical/genetic cell ablation, and a double transgenic line carrying both ERE: mCherry and cyp19a1b:GFP reporter genes, tg ( ERE:mCherry ; cyp19a1b:GFP ) ( Takesono et al, 2022 ) (listed in Table 1 ). The tg ( ERE:Gal4ff ; UAS:GFP ) in a pigment mutant Casper background substantially improves the visual clarity in estrogen responsive GFP expression in vivo as compared with the tg ( ERE:Gal4ff ; UAS:GFP ) in wild type background and has facilitated the detection sensitivity for the study of target tissues and potencies of a wide range of estrogenic chemicals ( Green et al, 2016 ; Green et al, 2018 ) and their EDC mixtures (in surface wastewaters) ( Cooper et al, 2021a ; Cooper et al, 2021b ). In the tg ( ERE:Gal4ff ; UAS:Kaede ) line the reporter protein, Kaede, can be photo-converted from green fluorescent to red fluorescent with a short UV exposure and this allows for time-sequenced and tissue specific ER/ERE-responses to be monitored at a desired timing or location in the live embryo-larvae.…”
Section: Tg Zebrafish As Nam For Assessing Eedc-related Developmental...mentioning
confidence: 99%
“…It is estimated that more than one hundred thousand xenobiotics are currently in regular use in the human population (33). Biosensor transgenic fish offer great potential for both mixture and temporal effects analyses for exposure to chemicals and their mixtures (34)(35)(36). Here we applied an Estrogen Responsive Element (ERE) -Green Fluorescent Protein (GFP) transgenic zebrafish (Danio rerio) model in a pigment free (Casper) strain of zebrafish [ERE-GFP-Casper; (37)] to investigate for health effects and life stage sensitivities following chronic and acute exposures to a WwTW effluent with known (measured) estrogenic content.…”
Section: Introductionmentioning
confidence: 99%